ANALYZING THE PROPERTIES OF A COMPOSITE OF PCL-GRAPHITE BY THE INJECTION MOLDING - Setyarini, Putu Hadi; Fariqi, Ikhwan Hafiz; Sonief, Achmad As’ad (International Journal of Mechanical Engineering Technologies and Applications, 2024)
Coral reefs are vulnerable to several natural phenomena such as ocean warming, acidification, coral diseases, and plastic pollution. In order to tackle these problems, scientists are now working on the development of biocomposites utilizing biodegradable polymers such as polycaprolactone (PCL). Graphite can be used in conjunction with PCL to enhance its characteristics. The work is centered around conducting water absorption experiments on a composite material consisting of PCL and graphite. The investigation employs PCL granular and graphite powdered materials. The materials undergo heating, crushing, and weighing processes to ascertain weight ratios. Next, the mixture is shaped into specimens. The product's shape and distribution of chemical constituents are analyzed using water absorption, hydrophobicity, FTIR, and SEM testing. The findings indicate that the water absorption diminishes as the concentration of graphite powder increases. An alloy containing 10% graphite had the highest water absorption rate. The hydrophobicity test assesses the ability of a specimen's surface to repel water by introducing NaCl droplets and observing droplet production. The contact angle value exhibits a direct correlation with the increase in graphite content. The FTIR study indicates that there are no changes in the functional groups, resulting in a limited connection between the PCL matrix and the graphite filler. The temperature during the injection molding process affects the microstructure of the polymer. Lower temperatures lead to reduced crystallization, whereas higher temperatures result in denser molecular groupings. Graphite is a highly suitable choice for use as a filler in a PCL matrix because of its layered structure, large surface area, and excellent capacity to effectively fill voids within the matrix.